Model Predictive Control Method With Auto-Tuning Weighting Factor For Bidirectional DC-DC Battery Chargers - Guler, Naki; Bayhan, Sertac; Komurcugil, Hasan (IEEE, 2024)
This paper proposes a model predictive control (MPC) method with an auto-tuning weighting factor for bidirectional DC-DC battery chargers. The reference current value of DC-DC converter is desired as a DC quantity by neglecting the inductor current ripple. Therefore, MPC changes the switch position to obtain zero error (between reference and predicted current values). Hence, excessive switching frequency occurs. The weighting factor is used to prevent excessive switching frequency in MPC methods devoted to controlling DC-DC converters. The relationship between the weighting factor and inductor current ripple is clarified for bidirectional DC-DC converters. Thus, the switching frequency is kept approximately constant by using the proposed auto-tuning weighting factor. The proposed approach is validated by simulation studies performed on MATLAB/Simulink platform. The results reveal that the proposed auto-tuning strategy significantly reduces the variations in switching frequency that occur under variations in the current reference and input voltage.
IEEE 18th International Conference on Compatibility, Power Electronics and Power Engineering (CPE-POWERENG) -- JUN 24-26, 2024 -- Gdynia, POLAND
Keywords: Battery charger; MPC; weighting factor tuning; current control